2003
DOI: 10.1007/bf02706217
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the neurotrophin receptors Trk A and Trk B in adult human astrocytoma and glioblastoma

Abstract: Neurotrophins and their receptors of the Trk family play a critical role in proliferation, differentiation and survival of the developing neurons. There are reports on their expression in neoplasms too, namely, the primitive neuroectodermal tumours of childhood, and in adult astrocytic gliomas. The involvement of Trk receptors in tumour pathogenesis, if any, is not known. With this end in view, the present study has examined 10 tumour biopsy samples (identified as astrocytoma, pilocytic astrocytoma and gliobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…Neurotrophin Trk A and Trk B receptors have been implied in tumor pathogenesis in an early stage. They respond to signals that elicit glial proliferation and are regarded as a factor of progression towards malignancy in low grade lesions where high levels of immunoreactivity are present 50 .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Neurotrophin Trk A and Trk B receptors have been implied in tumor pathogenesis in an early stage. They respond to signals that elicit glial proliferation and are regarded as a factor of progression towards malignancy in low grade lesions where high levels of immunoreactivity are present 50 .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It has been shown that expression of TrkA and TrkC correlates with a favorable outcome in neuroblastoma and medulloblastoma patients. In GBM, immunoreactivity for TrkA was shown to be inversely associated with the grade of malignancy (24). Moreover, TrkA overexpression was found to induce autophagic cell death that was mediated through the JNK pathway (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 By systematically screening a library of human tyrosine kinases for their oncogenic potential in astrocytoma formation and then characterizing functional features and molecular mechanisms associated with TrkB-induced oncogenesis, Ni et al have provided compelling findings indicating that TrkB can play a role in astrocytoma formation. 1 It is worth pointing out that previous studies not cited by Ni et al 1 had already identified an increase in TrkB expression in both low-grade astrocytoma and glioblastoma, 5,6 and a role for TrkB signaling in the growth of gliomas and other types of brain tumors or peripheral tumors of possible neural origin has been previously proposed. For example, BDNF-induced activation of TrkB increases the viability of brain-tumor stem cells (BTSCs) isolated from gliomas through activation of the extracellular-regulated kinase (ERK) and Akt pathways, whereas TrkB knockdown or pharmacological inhibition reduces BTSC growth and BDNF-dependent ERK activation.…”
Section: Targeting Tyrosine Receptor Kinase B In Gliomasmentioning
confidence: 91%